State-of-the-art and Prospects of Elastocaloric Cooling Technology - Qian Suxin; Yuan Lifen; Yan Gang; Yu Jianlin (Zhileng xuebao)
Elastocaloric cooling is a solid-state cooling technology based on the latent heat associated with the stress-induced phase transformation in elastocaloric materials. It is harmless to the environment, with remarkable theoretical system efficiency and cooling power density. Recently, rapid developments in elastocaloric cooling technology have been reported at research institutes in Europe and the USA. Some first-generation prototypes have been successfully developed and are properly functioning. As a guide for future related studies in China, this paper introduces the state-of-the-art and major challenges of this technology, including thermodynamic fundamentals, elastocaloric materials, prototype developments, and numerical simulations. Based on the literature, current elastocaloric refrigerators offer up to 14% Carnot cycle efficiency, a figure expected to exceed 30% in the near future; there is still significant potential for improvement when compared with the 80% Carnot efficiency offered by elastocaloric materials. Consequently, we can optimistically expect that elastocaloric cooling technology will experience faster growth and wider applicability in the future.